KINERJA BADAN LEGISLASI DPRD - Muslim '; Zaili Rusli (Jurnal Kebijakan Publik, 2013)
The purpose of this study was to analyze the strategiesused in order to improve the performance of Legislation Singingi Kuantan District Council 2009-2014. This study was conducted in Kuantan district legislature Singingi, where the informant researchis Regency Kuantan Singingi legislators and prominent intellectuals. Data collected by interviewand observation techniques, once the data collected were analyzed using descriptive analysis thatpromotes qualitative techniques. Results showed performance Legislation Singingi Kuantan districtlegislature is pretty good. While the dominant factor affecting the performance of the Kuantandistrict legislature Legislation Singingi are individual factors.